FOREIGN LANGUAGE READING ANXIETY AMONG THEOLOGY DEPARTMENT STUDENTS: CONTRIBUTING FACTORS AND ALLEVIATING STRATEGIES - Limeranto, Jeane Theresia; Subekti, Adaninggar Septi (LLT Journal: A Journal on Language and Language Teaching, 2021)
The study investigated factors contributing to English for Theology students’ Foreign Language Reading Anxiety (FLRA) and their strategies to alleviate it. This study was the continuation of a quantitative study involving 63 Theology student participants which found that their FLRA was significantly correlated with their reading achievement negatively. It was also conducted to fill the void in the FLRA literature in the Indonesian university context especially in Theology department necessitating learners to read a lot of passages in English, possibly quite anxiety-provoking for learners. Four selected participants from the previous quantitative study were interviewed and the data were analysed using Thematic Analysis. The study found that low self-confidence, lack of peer support, low self-perceived language competence, low motivation, and unfamiliar vocabulary increased learners' FLRA. Teachers' various methods, emphasising group activities were found to reduce their FLRA whilst whole-class reading activities tended to increase their FLRA. Furthermore, the uses of various reading strategies taught in class to comprehend texts were reported to reduce their FLRA to a certain extent depending on the degree of success of learners in using the strategies. Implications, limitations, and suggested directions for future studies were mentioned in light of the study's findings.